1991
DOI: 10.1111/j.1468-2257.1991.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisited Versus Compact Producer Service Firms: Insights from the French Case

Abstract: Much of the literature on the location of producer services is concerned with their uneven spatial development across regions. Although this approach is useful, it proves to be limited, and a complementary analytical framework is required. This paper uses data from France's Annual Survey of Services to address producer service location from a novel perspective, that of the firm. A basic distinction is made between single site (compact) and multisite (network) producer service firms, and the natures of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Research has shown the importance of major-client location for the location of producer service establishments within a metropolitan area (Coffey and Polese 1987;Illeris 1991;Lentnek et al1992;Leo and Philippe 1991;Monnoyer and Phlippe 1991). A key feature of metropolitan development in the late twentieth century has been employment suburbanization.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown the importance of major-client location for the location of producer service establishments within a metropolitan area (Coffey and Polese 1987;Illeris 1991;Lentnek et al1992;Leo and Philippe 1991;Monnoyer and Phlippe 1991). A key feature of metropolitan development in the late twentieth century has been employment suburbanization.…”
Section: Introductionmentioning
confidence: 99%
“…Given that a majority of the surveyed establishments are independent, single-site and locally owned, it is inevitable that an organisational set-up in the form of a 'network' is less frequently adopted. Arguably, not all establishments are capable of implementing a network strategy and not all activities lend themselves to it with the same ease (see also, Leo and Philippe, 1991). These establishments are essentially 'compact' in nature and the small establishment size (less than 25 employees) of the sample in Kuala Lumpur con rms this fact.…”
Section: Characteristics Of the Surveyed Establishmentsmentioning
confidence: 99%
“…Within the metropolitan area, however (i.e., within the commuting range of key personnel), location of service establishments depends on other characteristics. T h e location of major clients is widely cited as a key factor at this scale (Coffey and Polese 1987;Illeris 1991;Leo and Philippe 1991;Monnoyer and Philippe 1991;Lentnek et al 1992a, 199213). 0 huallachiin and Reid (1992) agreed that this explains the location of final demand services, such as for-profit health services and personal services.…”
Section: Lntrametropolitan Scalementioning
confidence: 99%